2013
DOI: 10.1176/appi.ps.201200208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Built Environment in Inpatient Psychiatric Wards

Abstract: Objective measurement of the built environment in inpatient psychiatric settings is feasible and can be used to identify features that increase user satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…26 It is clearly possible to collect large data-sets, but often other factors are not taken into account. For example, two studies using multilevel modelling on large ward samples (199 and 98 wards) 28,32 and one audit involving a large patient sample ( n = 602) 15 reported the presence of other confounding factors that were not addressed (differences in pharmacological regimes, differences in staff numbers and time patients spent in the assessed environments, respectively). Moreover, the long-term effects of design interventions were not monitored, with the exception of the Norwegian study, where the elimination of vandalism in the more home-like ward was shown to have persisted for at least a year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 It is clearly possible to collect large data-sets, but often other factors are not taken into account. For example, two studies using multilevel modelling on large ward samples (199 and 98 wards) 28,32 and one audit involving a large patient sample ( n = 602) 15 reported the presence of other confounding factors that were not addressed (differences in pharmacological regimes, differences in staff numbers and time patients spent in the assessed environments, respectively). Moreover, the long-term effects of design interventions were not monitored, with the exception of the Norwegian study, where the elimination of vandalism in the more home-like ward was shown to have persisted for at least a year.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the researchers suggested that the lack of patient perspectives may limit the applicability of the Ward Design Checklist tool for a broader evaluation of ward design. 32…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental psychologists have identified features in the built environments of psychiatric units that are related to rates of violence. Psychiatric staff recognize that non-corridor designs, which provide good visibility, create safer environments 73 . Nursing stations that are enclosed do not protect staff from violence; no change in the prevalence of aggression is observed when enclosed nursing stations are converted into open stations 74 …”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric staff recognize that non-corridor designs, which provide good visibility, create safer environments. 73 Nursing stations that are enclosed do not protect staff from violence; no change in the prevalence of aggression is observed when enclosed nursing stations are converted into open stations. 74 Other design features that can reduce violence include single-patient rooms and personal bathrooms.…”
Section: Psychopharmalogical Interventionsmentioning
confidence: 99%